2014
DOI: 10.1016/j.redox.2013.12.023
|View full text |Cite
|
Sign up to set email alerts
|

The role of Nox1 and Nox2 in GPVI-dependent platelet activation and thrombus formation

Abstract: BackgroundActivation of the platelet-specific collagen receptor, glycoprotein (GP) VI, induces intracellular reactive oxygen species (ROS) production; however the relevance of ROS to GPVI-mediated platelet responses remains unclear.ObjectiveThe objective of this study was to explore the role of the ROS-producing NADPH oxidase (Nox)1 and 2 complexes in GPVI-dependent platelet activation and collagen-induced thrombus formation.Methods and resultsROS production was measured by quantitating changes in the oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 44 publications
11
94
5
Order By: Relevance
“…Compared with WT mice, NOX2 KO mice showed no defects in neutrophil rolling and adhesion to the TNF-a-inflamed endothelium, but exhibited nearly complete inhibition of neutrophil-platelet interactions on the inflamed venules ( Figure 1B-E and supplemental Videos 1 and 2). Consistent with recent studies, 14 there were no differences in the number of circulating blood cells between WT and NOX2 KO mice (Table 1). These results indicate that intravascular NOX2 is critical for neutrophil-platelet association during vascular inflammation.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Compared with WT mice, NOX2 KO mice showed no defects in neutrophil rolling and adhesion to the TNF-a-inflamed endothelium, but exhibited nearly complete inhibition of neutrophil-platelet interactions on the inflamed venules ( Figure 1B-E and supplemental Videos 1 and 2). Consistent with recent studies, 14 there were no differences in the number of circulating blood cells between WT and NOX2 KO mice (Table 1). These results indicate that intravascular NOX2 is critical for neutrophil-platelet association during vascular inflammation.…”
Section: Resultssupporting
confidence: 92%
“…14 We found that the surface expression of GPVI and GPIba was also similar in WT and NOX2 KO platelets (supplemental Figure 2A-B). In addition, we observed that NOX2 deletion significantly decreased the surface expression of P-selectin and aIIbb3 integrin in response to 0.025 but not 0.05 U/mL thrombin ( Figure 3A and supplemental Figure 2C), suggesting that other signaling pathways induced by the increased concentration of thrombin compensate for the defective function of the KO platelets.…”
Section: Platelet Nox2 Regulates P-selectin Exposure Upon Agonist Stimentioning
confidence: 65%
See 1 more Smart Citation
“…[10][11][12][13][14] Signaling immediately downstream of GPIb-IX-V/GPVI involves activation of Src and Syk kinase-dependent tyrosine phosphorylation pathways and Src/Syk-dependent and Src/ Syk-independent generation of intracellular reactive oxygen species (ROS). [17][18][19][20] The cytoplasmic domains of GPIb-IX-V and GPVI directly bind to signaling or adaptor proteins, including phosphatidylinositol 3-kinase (via the p85 subunit) 21,22 and constitutively phosphorylated Lyn (via a proline-rich sequence of GPVI), 23 respectively. In the case of GPVI, ligand-induced receptor cross-linking enables active Lyn to phosphorylate Syk associated with the immunoreceptor tyrosine-based activation motif (ITAM) in the cytoplasmic domain of Fc receptor γ-chain, initiating canonical Syk-dependent signaling pathways.…”
Section: Platelet Activation and Thrombus Formation At The Vessel Wallmentioning
confidence: 99%
“…The behaviour of the tested particles in the microfluidic channel was monitored during the experiment using an AM-7013MZT microscope (Dino-Lite Digital Microscope, Naarden, the Netherlands). Representative images were evaluated using ImageJ analysis software (version 1.42) from the National Institutes of Health (Bethesda, Md., USA) [30].…”
Section: Behaviour Of Ha-coated Particles In the Channel Of A Microflmentioning
confidence: 99%